2018
DOI: 10.17482/uumfd.382516
|View full text |Cite
|
Sign up to set email alerts
|

Propi̇yoni̇k Asi̇ti̇n İzobuti̇l Alkol İle Amberlyst 36 Ve Amberlyst 70 Katali̇zörleri̇ Varliğinda Esterleşme Ki̇neti̇ği̇

Abstract: The esterification of propionic acid with isobutyl alcohol has been studied in a batch reactor in the presence of Amberlyst 36 and Amberlyst 70 catalysts. Reaction parameters applied in this study are speed of agitation (500-1000 rpm), particle size of catalyst (400-600 µm, 600+ µm), temperature (318-348 K) and catalyst loading (4-12 g-dry resin/L). A pseudo-homogeneous kinetic model was derived and all thermodynamic and kinetic parameters were calculated. Forward reaction rate constant for Amberlyst 36 and Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…These experimental results are in agreement with the work described by Orjuela et al, 40 which stated that the catalytic activity of Amberlyst 70 may overperform Amberlyst 15 in esterification reactions even though the former exhibits a lower pore volume and surface area. It was also found that Amberlyst 70 is a more effective catalyst in the esterification reaction than Amberlyst 36, consistent with the results obtained by Hoşgün and Çitak 53 in the kinetic study of propionic acid with isobutyl alcohol.…”
Section: Ion Exchange Resinssupporting
confidence: 88%
“…These experimental results are in agreement with the work described by Orjuela et al, 40 which stated that the catalytic activity of Amberlyst 70 may overperform Amberlyst 15 in esterification reactions even though the former exhibits a lower pore volume and surface area. It was also found that Amberlyst 70 is a more effective catalyst in the esterification reaction than Amberlyst 36, consistent with the results obtained by Hoşgün and Çitak 53 in the kinetic study of propionic acid with isobutyl alcohol.…”
Section: Ion Exchange Resinssupporting
confidence: 88%